2020
DOI: 10.1109/tnsre.2020.2983515
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Posture, Applied Force and Perturbation Direction on Hip Joint Viscoelasticity

Abstract: Limb viscoelasticity is a critical factor used to regulate the interaction with the environment. It plays a key role in modelling human sensorimotor control, and can be used to assess the condition of healthy and neurologically affected individuals. This paper reports the estimation of hip joint viscoelasticity during voluntary force control using a novel device that applies a leg displacement without constraining the hip joint. The influence of hip angle, applied limb force and perturbation direction on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The human central nervous system modulates muscle activation to generate the required torque and variable mechanical impedance at our joints to move and stabilize our motion [43]. Despite existing efforts in identifying mechanical joint impedance [44][45][46][47], multi-joint mechanical impedance have not yet fully uncovered during motion. In order to improve our simulations, the variable impedance can be also implemented in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The human central nervous system modulates muscle activation to generate the required torque and variable mechanical impedance at our joints to move and stabilize our motion [43]. Despite existing efforts in identifying mechanical joint impedance [44][45][46][47], multi-joint mechanical impedance have not yet fully uncovered during motion. In order to improve our simulations, the variable impedance can be also implemented in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors did not include neural parameters in their torque estimation model, and instead used measured EMG to estimate the neuromuscular activity due to stretch reflex. Recent advancements in joint mechanical impedance estimation during active movements [ 91 , 92 , 93 , 94 ] would allow further investigations on how spasticity affects the modulation of joint impedance, particularly joint stiffness and viscosity, during volitional movement and walking.…”
Section: Discussionmentioning
confidence: 99%
“…standing or seated. These experiments showed that joint impedance depends on various factors, including joint angles, joint velocities and muscle activity [9,13,33,6,29,5,25,30]. The results imply that joint impedance must vary during movement.…”
Section: Introductionmentioning
confidence: 88%
“…Joint impedance is estimated by measuring the response to mechanical perturbations applied to the joint by robotic devices and is often expressed in terms of joint inertia, damping and stiffness [19,10,23,6,9,13,33,7]. Identification of hip, knee and ankle joint impedance has previously been performed under static conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%